2020
DOI: 10.3167/latiss.2020.130203
|View full text |Cite
|
Sign up to set email alerts
|

Determining the impact of lecture videos on student outcomes

Abstract: The course materials students are expected to utilise in online instruction vary. Studies have shown that students tend to enjoy online courses with lecture videos more than those without, but few studies have measured the impact of lecture videos on student outcomes. Do lecture videos increase student understanding and retention, thus improving student outcomes? Students were provided with one or more study aids, video lecture, PowerPoint or instructor-created notes for learning about the role of the Electora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Previous research has shown that videos are one of the potential and effective educational tools (El-Ariss et al, 2021; Robertson & Flowers, 2020). Video-based learning enhances the students’ engagement, learning performance, and motivation (Scagnoli et al, 2017) and encourages self-directed and autonomous learning (van der Meij & Dunkel, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous research has shown that videos are one of the potential and effective educational tools (El-Ariss et al, 2021; Robertson & Flowers, 2020). Video-based learning enhances the students’ engagement, learning performance, and motivation (Scagnoli et al, 2017) and encourages self-directed and autonomous learning (van der Meij & Dunkel, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Jayaratne and Moore (2017) revealed that creating instructional videos was very helpful and preferred instructional activities for the students to learn online. Also, Robertson and Flowers (2020) showed in their study that lecture or instructional video with PowerPoint was the most effective study aid for the students.…”
Section: Resultsmentioning
confidence: 99%
“…One of the most popular methods of lecture adaptation for either fully remote or hybrid teaching has been providing prerecorded, narrated slides for students (Kizilcec et al, 2015; Robertson & Flowers, 2020). These lectures may also be accompanied by a Picture-in-Picture (PiP) video of the lecturer’s face in a corner of the screen (Baturay, 2015; Kizilcec et al, 2014).…”
Section: Research On Remote and Hybrid Lecture Deliverymentioning
confidence: 99%
“…Since the introduction of MOOCs in 2008 (Stevens, 2013), there has been an increase in research on online teaching. Many studies in this area have focused on best practices for presenting content on a learning management system (e.g., Dumford & Miller, 2018; Keengwe & Kidd, 2010; Sclater, 2008), and more recently, research has spotlighted the effects of recorded lecture delivery on student engagement and learning (e.g., Chen & Wu, 2015; De Rosa, 2021; Guo et al, 2014; Robertson & Flowers, 2020). Examinations of the different types of online multimedia learning and e-learning have identified key principles for maximizing user engagement (Chiu, 2022; Guo et al, 2014; Gutentag et al, 2022; Kokoç et al, 2020; Pi et al, 2017).…”
Section: Research On Remote and Hybrid Lecture Deliverymentioning
confidence: 99%